Conservation furrows and groundnut + redgram intercropping enhance productivity and profitability under rainfed semi-arid conditions: CONSERVATION FURROWS AND GROUNDNUT+REDGRAM INTERCROPPING IN RAINFED SEMI-ARID CONDITIONS - C RADHA KUMARI; B SAHADEVA REDDY; M VIJAY SANKAR BABU (Journal of Oilseeds Research, 2026)
Rainfed groundnut production in semi-arid India is constrained by erratic rainfall and frequent droughts. Afield study was conducted to assess the impact of conservation furrows in a groundnut + redgram (8:1) intercropping system. Treatments included furrows at different row intervals (every 1st to 12th row) along with a control. The study revealed that closer furrow intervals (particularly after every row) improved yield attributes (filled pods, kernel weight, shelling percentage), resulting in a 47% higher groundnut equivalent yield (GEY) and 171% higher net returns compared to the control. Overall, the integration of conservation furrows with intercropping enhanced rainfall-use efficiency, yield stability, and farm profitability, making it a viable climate-resilient strategy for semi-arid rainfed agriculture.